1995
DOI: 10.1136/gut.37.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine mRNA expression in the mucosa of treated coeliac patients after wheat peptide challenge.

Abstract: This study investigated the presence of mRNA coding for interferon gamma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 25 publications
6
53
0
2
Order By: Relevance
“…Moreover, relative to the proinflammatory cytokines, only low levels of mRNA for IFN-, IL-2, IL-4 and IL-5, cytokines which are normally associated with antigen-specific immune responses, were expressed in the patients and controls, either before or 4 h after gluten challenge. Although others noted an approximately two-fold increase in the number of cells in the lamina propria of the small intestine that express mRNA for IL-2, IFN-, TNF-and IL-6, 4 h following gliadin challenge [43], control subjects were not included in that report [43]. Further, it is possible that those increases reflected the migration of cells already expressing those cytokines to the site of gluten challenge in response to chemoattractant stimuli, rather than de novo induction of cytokine synthesis by antigen-specific T cells, since the numbers of cytokine-expressing cells, and not cytokine levels, were assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, relative to the proinflammatory cytokines, only low levels of mRNA for IFN-, IL-2, IL-4 and IL-5, cytokines which are normally associated with antigen-specific immune responses, were expressed in the patients and controls, either before or 4 h after gluten challenge. Although others noted an approximately two-fold increase in the number of cells in the lamina propria of the small intestine that express mRNA for IL-2, IFN-, TNF-and IL-6, 4 h following gliadin challenge [43], control subjects were not included in that report [43]. Further, it is possible that those increases reflected the migration of cells already expressing those cytokines to the site of gluten challenge in response to chemoattractant stimuli, rather than de novo induction of cytokine synthesis by antigen-specific T cells, since the numbers of cytokine-expressing cells, and not cytokine levels, were assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Since a correlation between the magnitude of villous atrophy and that of enterocyte apoptosis has been shown previously in untreated CD patients, 26 it is conceivable that, by degrading either interstitial ECM or basement membranes, 12 MMP-12 ultimately leads to the collapse of villous architecture and subsequent enterocyte shedding to the lumen. Furthermore, since MMP expression is highly dependent on cytokines 27,28 and gluten exposure in patients with CD rapidly elicits high levels of Th-1 cytokines, such as IFN-g, IL-2 and TNF-a, 13,14 we simultaneously determined the levels of IFN-g and TNF-a. Our results confirm a strong upregulation of IFN-g in active CD but not of TNF-a, the latter being in accordance with recent findings by Forsberg et al 29 who showed a suppression of TNF-a mRNA in this condition.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Even though a major role for MMPs in T-cell injury of the gut has already been shown in experimental models 10 and some MMPs have been found raised in CD, 11,12 a quantitative and wide assessment of MMPs in this pathological condition has never been performed. Similarly, the effect of the upregulation of T helper (Th)-1 cytokines 13,14 on the activation of these enzymes has never been investigated in celiac mucosa.…”
mentioning
confidence: 99%
“…CD is regarded as a T helper type 1 (Th1) disease because mucosal up-regulation of the interferon (IFN)-g pathway is seen [7][8][9]. We reported recently that mucosal up-regulation of IFN-g pathway remained elevated even 1 year after gluten-free diet (GFD), suggesting that activation of the Th1 response is triggered not only by dietary gliadin, but is associated more fundamentally with CD, being already present in potential CD and in treated CD [10].…”
Section: Introductionmentioning
confidence: 99%